18F-FDG PET/CT in Metastatic Pilomatrix Carcinoma. (December 2016) - Vadrucci, Manuela; Gilardi, Laura; Crivelli, Filippo; Baroli, Alberto; Lomuscio, Giuseppe
Abstract : Abstract: We describe the FDG PET/CT findings in an exceedingly rare case of metastatic pilomatrix carcinoma (PC). A 76-year-old man, who underwent incisional biopsy of a soft-tissue mass in the frontal scalp that revealed PC, was referred for an 18 F-FDG PET/CT scan for staging purposes. PET/CT showed areas of increased radiotracer uptake corresponding to frontal mass and unsuspected lung lesions, which were later confirmed as metastases from PC at histological analysis. Clinical condition deteriorated rapidly, and the patient died 3 months after the initial diagnosis.